SAKHII- Empowering Women with One-Tap Safety App - Goradiya, Uma; Pandey, Naman; Khan, Mantasha; Tiwari, Satyam; Pawar, Mandar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In India, numerous crimes targeting women occur daily. We are far from knowing the actual figures due to hundreds of cases that go unnoticed. Recognizing this pressing issue, the objective of this project is to develop a mobile application that can provide features of self-defense training techniques and emergency services access, such as locating the nearest police station, hospitals, bus stops, and pharmacies. It will include a list of emergency calling options to dial emergency numbers and real-time location sharing. When activated, the app will send the user’s location every 3 minutes and enable them to share their location with the nearest police station and government bodies with just one tap in case of an emergency. This application is integrated with numerous features in one app, playing a pivotal role in women’s safety while providing a user-friendly experience.